2009
DOI: 10.1111/j.1364-3703.2008.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of virulence genes in Fusarium oxysporum f. sp. lycopersici by large‐scale transposon tagging

Abstract: Forward genetic screens are efficient tools for the dissection of complex biological processes, such as fungal pathogenicity. A transposon tagging system was developed in the vascular wilt fungus Fusarium oxysporum f. sp. lycopersici by inserting the novel modified impala element imp160::gfp upstream of the Aspergillus nidulans niaD gene, followed by transactivation with a constitutively expressed transposase. A collection of 2072 Nia(+) revertants was obtained from reporter strain T12 and screened for alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 75 publications
2
37
0
Order By: Relevance
“…Recently homologs of three Foc pathogenicity genes, SIX genes called SIX1, SIX7 and SIX8 were identified by Meldrum et al (2012). Insertional mutant banks of Fol generated by inserting the novel modified impala element (fungal transposon) can be used for further investigation of pathogenicity genes (Lopez-Berges et al 2009). …”
Section: Fungal Defensementioning
confidence: 99%
“…Recently homologs of three Foc pathogenicity genes, SIX genes called SIX1, SIX7 and SIX8 were identified by Meldrum et al (2012). Insertional mutant banks of Fol generated by inserting the novel modified impala element (fungal transposon) can be used for further investigation of pathogenicity genes (Lopez-Berges et al 2009). …”
Section: Fungal Defensementioning
confidence: 99%
“…Generation and molecular characterization of the F. oxysporum Dfmk1, Dste12, and DmeaB mutants were described previously (Di Pietro et al, 2001;Ló pez-Berges et al, 2009;Rispail and Di Pietro, 2009). Fusarium graminearum isolate PH-1 and Magnaporthe oryzae isolate Guy-11 were used as indicated.…”
Section: Fungal Isolates and Culture Conditionsmentioning
confidence: 99%
“…Targeted replacement of the F. oxysporum MeaB gene in the Dfmk1 background was performed using a fusion PCR construct and protocol described previously (Ló pez-Berges et al, 2009). Targeted replacement of the entire coding region of the F. oxysporum AreA gene with the hygromycin resistance cassette under control of the A. nidulans GpdA promoter (PgpdA) and TrpC terminator (Ttrpc) was performed using the split-marker method (Catlett et al, 2003) following the protocol previously described (Rispail and Di Pietro, 2009) (see Supplemental Figure 7 online).…”
Section: Targeted Gene Knockoutmentioning
confidence: 99%
“…For cDNA synthesis, 1 g total RNA was reverse transcribed using the oligo(dT) [12][13][14][15][16][17][18] primer and SuperScript II (Invitrogen) according to the manufacturer's instructions. PCR mixtures contained 25 ng DNA, 5 pmol of each primer, 200 nM deoxynucleotide triphosphates, and 1 unit BioTherm DNA polymerase (GeneCraft GmbH, Lüdinghausen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that under conditions of nitrogen sufficiency MeaB activates nmrA expression by binding to a conserved sequence in the nmrA promoter, thus indirectly modulating AreA activity (43). MeaB orthologues have not yet been characterized in any other fungus, although recently meaB was identified by transposon tagging as a virulence factor in the plant pathogen Fusarium oxysporum (17), and in F. fujikuroi meaB was identified by microarray analysis as a gene whose transcription is regulated in response to nitrogen availability (32).…”
mentioning
confidence: 99%